Effect of Ground Handling Services on Arrival Baggage for Passenger Satisfaction - Prabowo, M Dwiky Aditya; Amalia, Direstu; Septiani, Virma; Komalasari, Yeti (Journal of Social Work and Science Education, 2023)
Numerous airline firms are fighting to raise the standard and reputation of their operations in response to the rising demand for air transportation services. The pre-flight and post-flight stages of an aircraft's operation require assistance from ground handling agents, affecting customer satisfaction with air transportation services. Passenger satisfaction is the expression of enjoyment or satisfied with the assistance received from the staff. This study's goal is to ascertain how much ground handling services offered by airlines during arrivals at General Ahmad Yani Semarang International Airport have an impact on passengers. This quantitative study aims to test the predetermined objectives on travelers from five airlines who employ PT. Kokapura's ground handling services. This study employed observation, questionnaires, and literature reviews as data collection methods. T-tests and the coefficient of determination are used to analyze the data (R2). With a calculated t-value of 21.182 > t-table 1.985, the study's findings demonstrate that the arrival baggage service offered by PT. Kokapura's ground handling significantly effects traveler satisfaction at General Ahmad Yani Semarang International Airport. The remaining 17.9 percent is influenced by other factors, with a correlation coefficient of 0.821 and an 82.1 percent coefficient of determination.